2019
DOI: 10.3174/ajnr.a6283
|View full text |Cite
|
Sign up to set email alerts
|

Imaging G-Ratio in Multiple Sclerosis Using High-Gradient Diffusion MRI and Macromolecular Tissue Volume

Abstract: BACKGROUND AND PURPOSE: Remyelination represents an area of great therapeutic interest in multiple sclerosis but currently lacks a robust imaging marker. The purpose of this study was to use high-gradient diffusion MRI and macromolecular tissue volume imaging to obtain estimates of axonal volume fraction, myelin volume fraction, and the imaging g-ratio in patients with MS and healthy controls and to explore their relationship to neurologic disability in MS. MATERIALS AND METHODS:Thirty individuals with MS (23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 37 publications
4
35
2
Order By: Relevance
“…3 ). B-type lesions are thought to be associated with more severe demyelination and axonal damage ( Yu et al, 2019 ). Therefore, the classification proposed would provide information regarding inflammatory destruction or the ability for neurorepair in a given patient, potentially representing a useful biomarker for phase II clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…3 ). B-type lesions are thought to be associated with more severe demyelination and axonal damage ( Yu et al, 2019 ). Therefore, the classification proposed would provide information regarding inflammatory destruction or the ability for neurorepair in a given patient, potentially representing a useful biomarker for phase II clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…( Assaf et al, 2008 ; Alexander et al, 2010 ; Huang et al, 2016 )). This has been used by Duval et al for g-ratio mapping in the spinal cord ( Duval et al, 2017 ) and by Yu et al ( Yu et al, 2019 ) in patients with multiple sclerosis. However, such a protocol requires more extensive (and time-consuming) data acquisition.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the challenges associated with accurate measurement and calibration of the MVF and AVF, many studies have exploited the potential of in vivo g-ratio weighted imaging for a variety of different applications (see Table 1 for full details). These have ranged from g-ratio mapping in infants ( Melbourne et al, 2016 ) and children ( Dean et al, 2016 ) to healthy adults ( Mohammadi et al, 2015 ; Mancini et al, 2018 ; Berman et al, 2019 ; Drakesmith et al, 2019a ), during healthy aging ( Cercignani et al, 2017 ; Berman et al, 2018 ) and as a result of pathological change ( Hagiwara et al, 2017 ; Hori et al, 2018 ; Kamagata et al, 2019 ; Yu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electron microscopy is the gold standard technique to measure the g-ratio; this limits investigations to ex vivo measures. To address this, new clinical magnetic resonance imaging (MRI)-based methods have been introduced for whole-brain in vivo mapping of the g-ratio and have shown that the g-ratio could represent a sensitive and specific biomarker of neurodevelopment and neurodegeneration (Berman, West, Does, Yeatman, & Mezer, 2018;Campbell et al, 2017;Cercignani et al, 2017;Colgan et al, 2016;Dean et al, 2016;Mustafi et al, 2019;Parker et al, 2018;Yu et al, 2019). The original approach was introduced by Stikov and colleagues and is based on measuring the axonal and myelin volume fractions in a voxel, instead of for individual fibers, and assuming a uniform g-ratio for all fibers (Stikov et al, 2011); this has come to be known as the "aggregate g-ratio" (Stikov et al, 2015), the calculation of which requires an estimation of myelin volume fraction (MVF) and axonal volume fraction (AVF).…”
Section: Introductionmentioning
confidence: 99%